Post–Pulmonary Embolism Syndrome: An Update Based on the Revised AWMF-S2k Guideline - Meyer, F. Joachim; Opitz, Christian (Hämostaseologie, 2024)
In survivors of acute pulmonary embolism (PE), the post-PE syndrome (PPES) may occur. In PPES, patients typically present with persisting or progressive dyspnea on exertion despite 3 months of therapeutic anticoagulation. Therefore, a structured follow-up is warranted to identify patients with chronic thromboembolic pulmonary disease (CTEPD) with normal pulmonary pressure or chronic thromboembolic pulmonary hypertension (CTEPH). Both are currently understood as a dual vasculopathy, that is, secondary arterio- and arteriolopathy, affecting the large and medium-sized pulmonary arteries as well as the peripheral vessels (diameter < 50 µm). The follow-up algorithm after acute PE commences with identification of clinical symptoms and risk factors for CTEPH. If indicated, a stepwise performance of echocardiography, ventilation–perfusion scan (or alternative imaging), N-terminal prohormone of brain natriuretic peptide (NT-proBNP) level, cardiopulmonary exercise testing, and pulmonary artery catheterization with angiography should follow. CTEPH patients should be treated in a multidisciplinary center with adequate experience in the complex therapeutic options, comprising pulmonary endarterectomy, balloon pulmonary angioplasty, and pharmacological interventions.
Keywords: pulmonary embolism; chronic thromboembolic pulmonary hypertension; chronic thromboembolic pulmonary disease; pulmonary endarterectomy; balloon pulmonary angioplasty